B152 Twenty-four hour provision of regional anaesthesia for rib fracture patients- a departmental survey. (11th August 2022) - Kausar, S; Hardwick, G; Fox, B
Abstract : Background and Aims: Early patient controlled analgesia (PCA) and regional anaesthesia (RA) are key for patients with severe rib fractures. In 2019, the Queen Elizabeth Hospital King's Lynn, implemented Thoracic Injury Pathway To Optimise Pain and physiotherapy (TIPTOP). As a part of this project, an electronic departmental survey was performed. Methods: In August 2021, all anaesthetists who provide on call cover were surveyed as to what analgesic strategy they would be happy to provide for rib fractures. Options included opioid PCA, off-label analgesics and RA blocks. Results: 28 of 38 anaesthetists responded (response rate 74%). All anaesthetic grades responded. Results are presented in table 1 . All respondents were happy to provide PCA. The next most common option was thoracic epidural (20, 71%) followed by intravenous Ketamine or Magnesium (both 18, 64%). Few were happy to provide a chest wall catheter such as Erector Spinae plane Block (7, 25%). Conclusions: Despite regular training sessions, when results were filtered to those providing resident out-of-hours cover, only 60% were happy to perform RA. As such a 24/7 analgesic service focusing on RA is not feasible. This mirrors the wider health-care community. A twitter poll last year found only 18% of departments offered reliable 24/7 access to RA for rib fractures (n = 210). We currently provide day-time RA via a team of regional anaesthetists and have optimised the non-RA options for out-of-hours admissions (e.g morphine-ketamine PCA). This work makes a strong argument for assessment and standardisation of provision via a National Audit Project.